ANTICANCER ACTIVITY OF POLYMERIC NANOPARTICLES CONTAINING ETOPOSIDE USING ALBINO RATS AS EXPERIMENTAL ANIMAL MODEL - T, Ayyappan; S, Shanmugam (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Etoposide is a potent anticancer drug and a major limiting factor that hinders therapeutic use as its high levels of systemic circulation often associated with various off-target effects, particularly cardiotoxicity. The present study focuses on the evaluation of the anticancer activity of optimized etoposide nanoparticles compared with marketed etoposide formulation in experimental animal models. Methods: Albino rats (180–200 g) were used for the study. The anticancer effect of the formulated etoposide nanoparticles was evaluated by induction of hepatocellular carcinoma (HCC). The animals housed in cages and kept on a 12 h light/dark cycle. Following the acclimatization for 1 week, HCC will be induced in rats by adding 100 mg/L of diethylnitrosamine (DENA) in drinking water for 8 weeks. Drug treatment (etoposide [9 mg/kg] in 0.5 % carboxymethyl cellulose; p.o.) can be started at the end of 1 week after cancer induction and dose of 9 mg/kg of etoposide and lyophilized nanoparticles will be administered through oral route on 1, 7, 14, 21, and 28 days. Nanoformulations were evaluated in healthy rats, and anticancer activity was studied in DENA treated rats. Results: The results showed that the polymeric nanoparticles containing etoposide was screened for its anticancer activity by counting the liver nodules of rats with hematoxylin and eosin stain when comparing control and etoposide-treated group. Conclusion: The results of the study concluded that in rats treated with nanoformulations, the numbers of liver nodules were found to be significantly reduced.